Toward the Transformation of the ELA Classroom - Ashley Wolstein (Study and Scrutiny, 2025)
Despite some calls for more inclusive reading lists, the written standards and high school reading lists often represent a Eurocentric perspective which can reinforce inequities perpetuated by the status quo. Many teachers are motivated to engage with critical literacy tools, but they often lack the background knowledge, teaching resources, and administrative support to carry out a critical curriculum or change canonical reading lists. This qualitative case study drew upon decolonial theory to explore how one secondary teacher and two of her ninth-grade language arts sections engaged with a critical questioning tool applied to a young adult novel  by an Indigenous author. I employed iterative thematic inquiry and analyzed data during and after collection. The analysis makes clear here the benefits of the tool in regards to transforming the ELA classroom: providing a process for critically engaging with literary texts and facilitating decolonial understandings. Implications include the following: (1) teachers need time, support, and training to enact a decolonial or critical curriculum and (2) further research needs to be conducted regarding the use of the critical questioning tool.